1990
DOI: 10.1007/bf01724797
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine concentration during sedation in ventilated patients requiring intensive therapy

Abstract: The effects of isoflurane and midazolam sedation on the catecholamine responses of ventilated patients were studied over a 24-h period. Sixty ventilated patients admitted to our intensive therapy unit were allocated randomly to receive either isoflurane or midazolam sedation. Arterial blood samples for plasma catecholamine concentrations were taken at baseline, 6 h after starting sedation and at the end of the study period. Patients sedated with isoflurane showed a progressive reduction in both adrenaline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
9
1
1
Order By: Relevance
“…The values of plasma norepinephrine and epinephrine found in this study agreed with previous values quoted in studies. 20,36,37 Kong et al 37 found higher values of catecholamines in critically ill patients; however, their patients had not been well sedated before measurement. The patients in the current study were well sedated with morphine/midazolam and had a mean Glasgow coma scale of 4.1 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…The values of plasma norepinephrine and epinephrine found in this study agreed with previous values quoted in studies. 20,36,37 Kong et al 37 found higher values of catecholamines in critically ill patients; however, their patients had not been well sedated before measurement. The patients in the current study were well sedated with morphine/midazolam and had a mean Glasgow coma scale of 4.1 (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Although such reversible psychomotor dysfunction after isoflurane sedation has been reported mainly in infants and children [8][9][10][11][12], and extremely rarely in adults [2][3][4][5][6][7]13], all of these reports are case reports [11][12][13], small-scale studies enrolling only 10 or 17 children [8][9][10], or only 20 or 30 adults [2][3][4][5][6][7], who received isoflurane for sedation. Therefore, we investigated the incidence of psychomotor dysfunction in a larger number of patients, including both children and adults, who were sedated with isoflurane during mechanical ventilation in the general ICU, and evaluated whether various factors, such as gender, age, duration of isoflurane sedation, minimum alveolar concentration (MAC)-hours of isoflurane, and drugs concomitantly used with isoflurane, could affect the incidence of psychomotor dysfunction after prolonged isoflurane inhalation.…”
Section: Introductionmentioning
confidence: 92%
“…Inhalation anesthetics also have been used for this purpose [1], and isoflurane appears to be particularly suited for prolonged sedation because of its low biological metabolic rate, low organ toxicity, and minimal adverse effects [2]. Isoflurane may be advantageous over IV sedatives, because it is associated with a more satisfactory degree of sedation [3], more effective suppression of catecholamine release [4], shorter time to extubation [2,3,5,6], less likelihood of tachyphylaxis, withdrawal, and abstinence syndromes [5], and fewer hallucinations/delusions in the long-term followup [7], compared with midazolam or midazolam-fentanyl. Its bronchodilator action is also useful for both treatment and sedation of asthmatic patients requiring mechanical ventilation [8].…”
Section: Introductionmentioning
confidence: 98%
“…In such situations, undesirable pressure decrease, both by halothane-induced myocardial depression and by isoflurane-induced vasodilation, may be treated with volume infusion, associated or not to dopamine infusion. Still, a study published in 1990 19 comparing continuous sedation and midazolam or isoflurane, has reported significant epinephrine plasma concentration decrease in the isoflurane group. Apart from pressure decrease, especially in hypovolemic patients for whom it is counterindicated, special care should be taken to avoid environmental pollution with halogenates.…”
Section: Inhalational Agentsmentioning
confidence: 98%
“…Nestas situações, a redução indesejada da pressão arterial, seja por depressão miocárdica no uso do halotano seja por vasodilatação no uso do isoflurano, pode ser tratada com infusão de volume associada ou não à infusão de dopamina. Ainda, estudo de 1990 19 comparando sedação contínua com uso de midazolam ou isoflurano relatou diminuição significante da concentração plasmática de adrenalina no grupo que recebeu isoflurano. Afora a redução pressórica, particularmente nos pacientes hipovolêmicos, nos quais sua utilização é contra-indicada, cuidados especiais devem ser tomados no sentido de evitar a poluição ambiental devido ao uso dos halogenados.…”
Section: Agentes Inalatóriosunclassified